Systematic Literature Review and Meta-Analysis: The Effectiveness of Project-Based Learning in Science Learning - Lusy Tunik Muharlisiani; Susantinah Nugrahini Wisnujati; Titik Purwati; Kartini Marzuki; Bachtiar Nasution; Tomi Apra Santosa (Postgraduate, University of Mataram, 2023)
This study aims to determine the effectiveness of the project-based learning model in science learning. This type of research is systematic literature review (SLR) research and meta-analysis. The source of data in this study came from 653 articles obtained 24 articles that met the criteria. The process of searching for data sources comes from the databases of google scholar, Taylor of Francis, Wley, ERIC, and ScienceDirect. Data selection process with PRISMA method. The inclusion criteria in this meta-analysis are that research must come from Scopus indexed journals and Science and Technology Index (SINTA), Research published from 2020-2023, Research must have an experimental class of project based learning models and conventional learning control classes, research must have complete data to calculate the value of effect size. Analyze data with the help of JSAP applications. The results concluded that the summary effect value or mean effect size was 0.86 with large criteria. This finding is that the project-based learning model can improve students' science learning ability.